Burnout in mental health professionals : the roles of psychological flexibility, awareness, courage, and love - Ortiz Fune, Carmen (Colegio Oficial de Psicólogos de Madrid, 2020)
The predominant model of burnout posits three dimensions: emotional exhustion (EE), depersonalization (D), and (a lack of) personal accomplishment (PA). To date, contextual behavioral approaches have explored the role of psychological flexibility within this model of burnout but has not focused on the role of interpersonal variables, such as suggested by the Awareness, Courage, and Love (ACL) model of Functional Analytic Psychotherapy. In this study, 269 Spanish mental health workers completed a questionnaire study exploring the unique contribution of ACL, over and above psychological flexibility, to understanding burnout. Results indicated that psychological flexibility predicted all three dimensions of burnout. Regarding ACL, love was the strongest predictor of D over and above psychological flexibility and all three ACL dimensions contributed to PA prediction. We briefly present a contextual-behavioral model that integrates these findings with implications for improving interventions to reduce burnout in mental health practitioners.